Case Report: Response to Immunotherapy and Anti-Androgen Therapy in Male Occult Triple-Negative Breast Cancer - Wang, Xin-Hua; Zhang, Jing; Wu, Jie; He, Xiao-Han; Shen, Yan-Ru; Peng, Yong-Gang; An, Yu-Zhi (Frontiers in Oncology, 2022)
Male occult triple-negative breast cancer (TNBC) is an exceedingly rare form of breast cancer, and prospective information regarding its management is therefore lacking. Current treatment strategies are largely extrapolated from clinical trials of female breast cancer, leading to substantial knowledge gaps concerning the optimal management of male breast cancer. Here, we present a male patient with occult TNBC who responded to immunotherapy, with an obvious reduction in his tumor burden following antiandrogen therapy, after heavy treatment with several lines of chemotherapy. This case highlights the potential efficacy of immunotherapy in cases of male TNBC and suggests a role for antiandrogen therapy in managing patients with luminal androgen receptor-positive TNBC.